2020
DOI: 10.1093/brain/awz412
|View full text |Cite|
|
Sign up to set email alerts
|

Modelling brain development to detect white matter injury in term and preterm born neonates

Abstract: Premature birth occurs during a period of rapid brain growth. In this context, interpreting clinical neuroimaging can be complicated by the typical changes in brain contrast, size and gyrification occurring in the background to any pathology. To model and describe this evolving background in brain shape and contrast, we used a Bayesian regression technique, Gaussian process regression, adapted to multiple correlated outputs. Using MRI, we simultaneously estimated brain tissue intensity on T1- and T2-weighted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 50 publications
3
52
0
Order By: Relevance
“…The argument that essentially every brain is different is not novel, and the expectation that the effects of preterm birth are homogeneous and exactly alike in every infant is equally untenable 7,10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The argument that essentially every brain is different is not novel, and the expectation that the effects of preterm birth are homogeneous and exactly alike in every infant is equally untenable 7,10 .…”
Section: Discussionmentioning
confidence: 99%
“…To understand brain development at an individual level, offer accurate prognosis of later outcome, and study the effects of clinical risks and interventions, it is necessary to provide a personalized assessment of cerebral maturation 10 . Indeed, an unwarranted assumption that preterm birth has a homogenous effect on brain development might account for the relatively poor predictive power of neonatal MRI for later outcome, especially in the absence of major focal lesions 11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the brain maturation index may be a useful tool to capture potential delays and disorders in structural connectivity which may have a lasting impact on later neurological outcomes. Recent studies have shown the potential of normative modelling to find individual alterations in preterm babies (Dimitrova et al, 2020;O'Muircheartaigh et al, 2020), which are characterised by heterogeneous brain changes. In a similar way, we suggest that for an individual subject, a high deviation from the population norm, translating to age predictions significantly lower than true age (negative brain maturation index) can be a marker of potential developmental delay so that these subjects should undergo further tests and may need follow up.…”
Section: Brain Maturation Indexmentioning
confidence: 99%
“…Of course, correlations between groups are of less value to the practicing clinician than positive and negative predictive values for individuals, and, as with other similar studies, the individual predictive power of Kline et al ’s measurements is modest, probably largely due to significant intersubject variability. However, new modelling and machine learning techniques are beginning to make personalised image analysis more tractable, and there is hope that a better understanding of the clinical impact of encephalopathy of prematurity in each patient will soon be possible 6. In the meantime, Kline et al remind us again as we stand at the cotside that while haemorrhage and periventricular leucomalacia are not unimportant, we should be increasingly concerned with brain growth and maturation.…”
mentioning
confidence: 99%